The Concept of Labor Migration, Regulated and Unregulated Migration, the Development of the Legislative Framework in the Field of Labor Migration - Murodova D.O (Genius Journals, 2022)
This article discusses the issues of labor migration, the reasons for people to temporary migration, as well as the positive and negative effects of external labor migration. It is also said about the development of the Legislative Framework in the field of labor migration.
Keywords: Foreign Affairs; Labor; Integration; Language Of The Country